The Ideology of a Nation of Immigrants and the Issue of Employment in Aviva Chomsky’s “They Take our Jobs”! And 20 Other Myths about Immigration. - NDIAYE , Emmanuel Ngor (International Journal of Scientific Research and Management (IJSRM), 2020)
This study explores the postulate studied in Aviva Chomsky’s “They Take our Jobs"! And 20 Other Myths about Immigration. It examines the assumptions and arguments that fuel the public discourse about U.S. immigration. As noted by Chomsky, those arguments are based on myths that should be deconstrued to better understand the rationale behind the anti-immigrant rhetoric which is reflected by stereotypes such as immigrants take American jobs, drain down wages, or represent a threat to the social order and national security. On the basis of these arguments and information drawn from diverse sources, we have shown how from a nation of immigrants, America has become a country where immigrants take American jobs. Thus, the idea of the nation of immigrants refers specifically to immigrants of European ancestry, in particular those from northwestern Europe. The latter, also known as the WASP, represent the American mainstream culture and their hegemony is widespread to the point of influencing other sectors where decision-making processes echo the legacy, the values and expectations of the white community. Starting from these arguments, it can be stated that Anglo-Saxonism is fundamentally based on the domination of other communities and the institutions and ideologies of the United States reflect this reality.